Epidemiology of Enuresis among Children in Diyala Governorate - S Salahaldeen , Enas; Gh Noaman , Nadhim; SH Al-Zuheiry, Mehdi (Diyala Journal of Medicine, 2021)
Background: Nocturnal enuresis, is intermittent involuntary voiding in a child aged five years or more. One time a month for three months is required for the diagnosis. It is a common problem in children. It is the cause of stress for them and for their families. Enuresis can be classified into two types to understand its causes and treatment. These types are primary and secondary enuresis, monosymptomatic and polysymptomatic. Primary enuresis always associated with a familial history of delayed control of the urinary bladder. Secondary enuresis may cause by urinary tract or neurogenic causes like the spinal cord and urinary tract infection. Most of the cases were of the primary type. Objective: To evaluate the associated factor of nocturnal enuresis, study the various types of nocturnal enuresis, and evaluate the associated factors that affect the types of nocturnal enuresis. Patients and Methods: A cross-sectional study conducted in outpatient clinic of Albatool hospital in Diyala province, Iraq, 150 children was eligible in the study, which started from 1st Febreuary to 30th June 2020. Collection of the data was done by interview parents’ or the children's caregiver by a questionnaire that was used before for study enuresis. Analysis was carried out using statistical package for social sciences SPSS version 24. Results: The present study included 150 patients with enuresis, their mean age was 7.51±1.34 years (range:= 5-10 years), there were (59.3%) males and (40.7%) females. Most of the patients (61.3%) had 2-3 sibling, second in their birth order (52%), reside in the urban area (56%), a majority of the mothers 38% had primary school as their highest educational attainment, a majority of the fathers (32.7%) had secondary school as their highest educational attainment, most of the mothers 62.7% were housewives and 57.3% of fathers were employees. Regarding clinical features of the patients, 32% had a family history of enuresis, 52% had a history of fluid consumption other than water, 7.3% had a history of punishment, 8% had history of constipation, 27.3% had a history of emotional stress, 5.3% had a history of DM, 30.7% had a history of drug intake, 61.3% reveal UTI in their urinalysis, 78% reveal abnormal US findings. Secondary enuresis was found in 65.3% of the patients, while primary enuresis found in 34.7% of the patients, 7.3% of the patients complaining of diurnal enuresis. All studied factors not significantly associated with types of enuresis except constipation was found more in patients with secondary enuresis 91.7%. Conclusion: According to the previous study many risk factors were associated with nocturnal enuresis, in the current study these risk factors, except constipation which was associated with secondary enuresis, were not associated with nocturnal enuresis.